Regional aspects of fetal morphometry depending on climatic factors in a temperate continental climate - E. M. Iutinskiy; L. M. Zheleznov; S. A. Dvoryanskiy (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Relevance. Climate change and its seasonal fluctuations significantly affect the development of the fetus, affecting the morphometric parameters and the weight of the newborn. In the conditions of the temperate continental climate of the Kirov region, climatic factors such as air temperature, daylight hours and solar radiation levels can have a significant impact on the physiological processes in pregnant women and, as a result, on the growth and development of the fetus.Goal. To identify the relationship between climatic conditions, morphometric parameters of the fetus and the weight of the newborn in the temperate continental climate of the Kirov region.Object and methods. The study included 1,200 pregnant women without pronounced obstetric and extragenital pathology who underwent at least two ultrasound examinations during pregnancy. The main morphometric parameters of the fetus were evaluated: biparietal size (BPR), frontal-occipital size (LPR), head circumference (OH), abdominal circumference (OH) and femoral length (DBК). Climatic data (average temperature, number of sunny days and length of daylight) for each trimester were obtained based on the climatic characteristics of the Kirov region.Results. The analysis revealed a positive correlation between the temperature of the first trimester and fetal BPR, as well as between the number of sunny days in the third trimester and fetal coolant. Single-factor analysis of variance showed statistically significant differences in the average weight of newborns between the groups. Regression analysis confirmed that the temperature of the first trimester and the number of sunny days in the third trimester are significant predictors of birth weight, explaining 18% of its variation.Conclusions. The climatic conditions of the temperate continental climate of the Kirov region have a significant impact on the morphometric parameters of the fetus and the weight of the newborn. Low temperatures and a limited number of sunny days in the first trimester can slow down early fetal growth, especially the development of the bone system. Favorable climatic conditions in the third trimester, including higher temperatures and an abundance of sunlight, contribute to an increase in fetal weight and an improvement in its morphometric parameters. Taking into account seasonal climatic factors in pregnancy management in regions with pronounced seasonality can help optimize perinatal outcomes and develop personalized recommendations for pregnant women.